(untitled) (Editora Impacto Científico, 2025)
The genus Aspergillus is widely distributed in the environment and can cause infections ranging from allergic reactions to invasive and potentially fatal forms, especially in immunocompromised patients. Patients with immunosuppression, such as those with prolonged neutropenia, HIV or undergoing transplants, are highly susceptible to fungal infections due to the failure of the immune response. Thus, the reduction in neutrophils and the dysfunction of cellular immunity compromise control of the infection, favoring its progression. HIV aggravates this situation by reducing CD4+ T cells and weakening the immune system, making patients vulnerable to opportunistic infections, including Aspergillus. Despite antiretroviral therapy, many still have advanced immunosuppression, especially in low-income countries, increasing AIDS-related mortality. The inadequate management of these infections highlights the need for effective diagnostic and therapeutic strategies. This review aimed to explore the relationship between immunosuppression caused by HIV and susceptibility to Aspergillus infections, highlighting the impacts on patient health.